Operating Capacity, Profitability, Debt Ratio, dan Likuiditas berdampak kepada Financial Distress di masa Pandemi Covid-19 - Sheirlla Angela Giovanni; Indra Arifin Djashan (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
The purpose of this study is to provide empirical evidence related the effect of independent variables on financial distress in manufacturing companies in Indonesia. The independent variables used in this study are profitability, leverage, liquidity, operating capacity, sales growth, company size, audit committee, audit committee meetings, and independent commissioners. The research data comes from the financial statements and annual reports of manufacturing companies listed on the Indonesia Stock Exchange for three periods, from 2019 to 2021. The sample selection in this study used a purposive sampling technique and obtained a sample of 135 companies with a total data of 405. This study used multiple regression analysis to examine variables that affect financial distress as measured by the Altman Z-Score. The results of this study indicate that Profitability, Leverage, Liquidity, and Operating Capacity affect financial distress. However, Sales Growth, Company Size, Audit Committee, Audit Committee Meetings, and Independent Commissioners have no effect on Financial Distress.